A leading role for NADPH oxidase in an in-vitro study of experimental autoimmune encephalomyelitis. (April 2016) - Seo, Ji-Eun; Hasan, Mahbub; Rahaman, Khandoker Asiqur; Kang, Min-Jung; Jung, Byung-Hwa; Kwon, Oh-Seung
Highlights: Exposure of MOG35–55 emulsion increased NADPH oxidase activity, MMP-9 activity, ICAM-1, and VCAM-1. NADPH oxidase affected MMP-9, ICAM-1, and VCAM-1 expression, but not vice versa. NADPH oxidase inhibition exhibited the highest decrease in BBB permeability. NADPH oxidase plays a key role in BBB disruption in EAE-mimicking cell culture condition. Abstract: Myelin oligodendrocyte glycoprotein peptide fragment 35–55 (MOG35–55 ) is a major autoantigen inducing experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis that is characterized by blood–brain barrier (BBB) disruption. Various experimental approaches have employed MOG35–55 in vivo; however, in vitro BBB models using MOG35–55 are rarely reported. We investigated MOG35–55 exposure effects with complete Freund's adjuvant (CFA) and pertussis toxin (PTX) on brain endothelial cells and elucidated the relationships among NADPH oxidase, MMP-9, ICAM-1, and VCAM-1. These 4 factors significantly increased in MOG35–55 + CFA + PTX-exposed endothelial cells compared with the control cells. NADPH oxidase inhibition using apocynin reduced MMP-9 activity, ICAM-1, and VCAM-1. MMP-9 inhibitor I decreased expression of ICAM-1 and VCAM-1, and both anti-ICAM-1 and anti-VCAM-1 inhibited MMP-9 activity. Inhibitions of MMP-9, ICAM-1, and VCAM-1 did not change NADPH oxidase activity. Although inhibition of these 4 factors decreased BBB permeability in cells, inhibition of NADPH oxidase exhibited the highest decrease among these. NADPH oxidase directly influenced MMP-9, ICAM-1, and VCAM-1, but not vice versa. MMP-9 and the cell adhesion molecules reversibly affected each other. In conclusion, NADPH oxidase-derived superoxide elevated expression of MMP-9, ICAM-1, and VCAM-1, and these interactions can finally result in increases of BBB permeability in MOG35–55 + CFA + PTX-exposed endothelial cells.